Fish diversity along streams in Ulu Muda Forest Reserve, Kedah, Peninsular Malaysia - Khaironizam, Md Zain; Abdullah Halim, Muhammad Rasul; Fahmi-Ahmad, Muhammad; Aqmal-Naser, M.; Faraha, Intan; A Zakaria, Zahar; Norhakim Lokman, Mohd Ilham; Amal Azmai, Mohammad Noor; B Ahmad, Amiruddin (Malaysian Nature Society, 2021)
A survey on fish diversity was conducted at eight streams flowing into Muda Reservoir, one of the three reservoirs in the Ulu Muda Forest Reserve, Kedah. Forty-nine species from 24 fish families, including 10 new records for the area were recorded bringing the total number of fish species identified known to date to 63 species. Cypriniforms were the most dominant group of fish with 27 species, followed by siluriforms and anabantiforms with 11 and 10 species, respectively. A little-known species, Tuberoschistura baenzigeri, was reported for the first time in the west coast region of Peninsular Malaysia. This study was far from complete, but the results should be useful for local fisheries managers to manage the fish resources in Muda Reservoir and its tributaries for conservation and the benefit of local inland fishermen.